Síntese e avaliação antimicrobiana de derivados isoxazóis - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The synthesis of heterocyclic compounds, which has nitrogen and oxygen in its structure has been studied in the last few years. Among these researches, the ones derivative from isoxazole stands out. It is part of many drugs as cloxacillin, dicloxacillin, Valdecoxib, Leflunomide among other medicines for the treatment of different diseases. The type 3,4-disubstituted isoxazole-5(4H)-ones is presented as synthetic compounds with different applicability with physical, chemical and biological properties. There are many methodologies for attainment of these compounds, which the multicomponent reaction (MCR) stands out. MCRs are reactions that occur in a process called “one pot”. They are convergent and occur in moderate conditions. Many catalytic methodologies have been developed to improve the synthesis of these compounds and ionic liquids are taken as promising candidates for green and sustainable processes. Thus, the present article describes the synthesis of 3,4-disubstituted isoxazol-5 (4H) -one derivatives using an ionic liquid as a reaction promoter. Experiments were used to investigate the best conditions of formation of these products. The ionic liquid PEI.LI proved an efficient reaction catalyst in this type of reaction, due to its basic characteristic. The MCR provided varied throughput (34 up to 98%) and occurred in moderate conditions, as they did not require high temperatures or exhaustive reaction time. It was launched by a sustainable catalyst and used water as solvent, contributing to the principles of green chemistry. The spectroscopic analysis in the infrared region and 1H and 13C NMR analyzes allowed the characterization of the obtained compounds. The synthesized derivatives also have biological properties such as antibacterial activity.
Keywords: Isoxazol-5 (4H)-ona 3,4-dissubstituídos; Líquidos iônicos; Atividade antimicrobiana; 3,4-disubstituted isoxazol-5 (4H) -one; Ionic liquids; Antimicrobial activity; CIENCIAS EXATAS E DA TERRA::QUIMICA